2023
DOI: 10.1111/psyp.14260
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac timing and threatening stimuli influence response inhibition and ex‐Gaussian parameters of reaction time in a Go/No‐go task

Abstract: Sensorimotor responses vary as a function of the cardiac cycle phase. These effects, known as cardiac cycle time effects, have been explained by the inhibition of cardiac afferent signals on information processing. However, the validity of cardiac cycle time effects is challenged by mixed findings. Factors such as current information processing and affective context may modulate cardiac cycle time effects and account for inconsistencies in the literature. The current study examines the influence of cardiac cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 117 publications
0
5
0
Order By: Relevance
“…In a neutral stop-signal-task, Rae et al (2018) found response inhibition efficiency to be increased when stop stimuli were presented during systole. On the other hand, Yang et al (2023) found response inhibition to be decreased during systole in a comparable Go/No-Go paradigm. However, only in response to threat stimuli are known to benefit from facilitated processing during systole (Critchley & Garfinkel, 2015;Garfinkel et al, 2014;Garfinkel & Critchley, 2016).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In a neutral stop-signal-task, Rae et al (2018) found response inhibition efficiency to be increased when stop stimuli were presented during systole. On the other hand, Yang et al (2023) found response inhibition to be decreased during systole in a comparable Go/No-Go paradigm. However, only in response to threat stimuli are known to benefit from facilitated processing during systole (Critchley & Garfinkel, 2015;Garfinkel et al, 2014;Garfinkel & Critchley, 2016).…”
Section: Discussionmentioning
confidence: 85%
“…On the other hand, Yang et al. (2023) found response inhibition to be decreased during systole in a comparable Go/No‐Go paradigm. However, only in response to threat stimuli are known to benefit from facilitated processing during systole (Critchley & Garfinkel, 2015; Garfinkel et al., 2014; Garfinkel & Critchley, 2016).…”
Section: Discussionmentioning
confidence: 97%
“…The presented results indicate that consistency of video valance and emotional face can significantly increase ex-Gaussian parameter τ . According to prior work, attentional or intentional processes can be captured by the exponential tail of the distribution (i.e., τ ) [50] . Specifically, high values of τ index greater lapses in sustained attention [13] , [50] .…”
Section: Discussionmentioning
confidence: 99%
“…According to prior work, attentional or intentional processes can be captured by the exponential tail of the distribution (i.e., τ ) [50] . Specifically, high values of τ index greater lapses in sustained attention [13] , [50] . In our experiment, greater τ indicates more trials of long RT for participants to withdraw attention from stimuli when it is consistent with participants' current emotional state, which aligns with existing literature [1] , [3] , [26] , [39] , [42] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation